Effect of dilution rate on ethanol production by Saccharomyces cerevisiae(wild strain). - Abdul Samah, Othman; Abdul Rahman, Abdul Rashid (1990)
At a dilution rate of 0.02 h-1 ethanol production was 47.5g 1-1 while this increased rapidly to 60g 1-1 due to lesser inhibitory effects of ethanol on the growth of the organism. Maximum level of 70g-1 was attained when the dillution rate was 0.2h-1. A possible explanation for this is that the activity of alcohol dehydrogenase increase at such low dilution rates. However it would appear that once the ethanol levels reached 60-70g 1-1,significant inhibition occure resulting in declining biomass and increasing glucose and sucrose levels respectively.